Promoting Physical Activity to Lower the Incidence of Major Non-Communicable Diseases – A Literature Review to Inform a Simulation Model for Policy Purposes (Baltic Journal of Sport and Health Sciences, 2026)
Purpose: To predict the impact of physical activity (PA) policy in the Netherlands on health outcomes, quality of life, and costs, the Dutch National Institute for Public Health and the Environment developed a model incorporating PA effects across various health outcomes. For model input, we analysed recent literature on the association between PA and major non-communicable diseases.Methods: For this review, we systematically searched PubMed and Embase from 2016 to 2025 for meta-analyses on the dose–response association between PA and incidence of type 2 diabetes, stroke, ischemic heart disease, congestive heart failure, breast cancer, colon cancer, and dementia. The meta-analyses: 1) preferably included prospective cohort studies, 2) reported a broad range and dispersion of PA levels, 3) expressed PA in MET-min/week, and 4) presented associations as hazard rate ratios (HRR) or relative risks (RR) versus inactivity. Eligible studies were appraised on methodological quality (low, moderate, high), sample size, data quality, generalisability to the Dutch population, and biological plausibility. Data from the highest-quality, most comparable study to the Dutch population was used to estimate the corresponding association in the model.Results: Kyu et al. (2016) reported that higher total PA (